2004
DOI: 10.1002/mrm.10710
|View full text |Cite
|
Sign up to set email alerts
|

T2 and T MRI in articular cartilage systems

Abstract: T2 and T1rho have potential to nondestructively detect cartilage degeneration. However, reports in the literature regarding their diagnostic interpretation are conflicting. In this study, T2 and T1rho were measured at 8.5 T in several systems: 1) Molecular suspensions of collagen and GAG (pure concentration effects): T2 and T1rho demonstrated an exponential decrease with increasing [collagen] and [GAG], with [collagen] dominating. T2 varied from 90 to 35 ms and T1rho from 125 to 55 ms in the range of 15-20% [c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
213
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(220 citation statements)
references
References 30 publications
5
213
1
Order By: Relevance
“…However, other work implies that T 1 is sensitive to biologically meaningful changes in cartilage, but is not specifically associated with any one inherent tissue parameter (35). They showed that T 1 is affected by the concentration, particularly of collagen, as well as by changes at the molecular level, and that hydration and structure also play a role (35). In the present study the small sample size may explain the lack of correlation between T 1 and proteoglycan content.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…However, other work implies that T 1 is sensitive to biologically meaningful changes in cartilage, but is not specifically associated with any one inherent tissue parameter (35). They showed that T 1 is affected by the concentration, particularly of collagen, as well as by changes at the molecular level, and that hydration and structure also play a role (35). In the present study the small sample size may explain the lack of correlation between T 1 and proteoglycan content.…”
Section: Discussioncontrasting
confidence: 58%
“…The results from this study demonstrate that T 1 can track proteoglycan content in vivo. However, other work implies that T 1 is sensitive to biologically meaningful changes in cartilage, but is not specifically associated with any one inherent tissue parameter (35). They showed that T 1 is affected by the concentration, particularly of collagen, as well as by changes at the molecular level, and that hydration and structure also play a role (35).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, different types of multiple quantum (MQ) coherence transfer methods have been developed to characterize this interaction. However, due to an order of magnitude low SNR of MQ filtered methods, their applications have been largely limited to ex vivo studies and some imaging experiments that were performed on highly ordered tissue such as tendons (86,219). Spin-locking methods to characterize this interaction offer high SNR (comparable to single quantum coherence) and can be implemented in vivo with relative ease.…”
Section: Mechanism Of T 1r Relaxation In Cartilagementioning
confidence: 99%
“…In the inset, the same graph is presented with its y-axis drawn in a logarithmic scale. From Keinan-Adamsky et al (29) It should be mentioned that in most cases of articular cartilage imaging, the TE used to obtain T 2 maps is relatively long (usually >8 ms) (30)(31)(32)(33). This may be the reason why the bi-exponential nature of the decay curve in the deep radial zone was overlooked in most studies and T 2 values calculated in this region are relatively long.…”
Section: The Nature Of 1 H T 2 Decay In Articular Cartilagementioning
confidence: 99%